Relationship between Permeability Coefficient and Fractal Dimension of Pore in Ionic Rare Earth Magnesium Salt Leaching Ore - Dan Wang; Yunzhang Rao; Liang Shi; Wei Xu; Tao Huang (Geofluids)
The change of permeability coefficient of ionic rare earth ore is one of the most important factors causing the uncontrollable flow of leaching solution, and the variation of pore structure of the ore body has a great influence on the permeability coefficient. The research on the evolution of the relationship between pore structure and permeability coefficient of ionic rare earths is of great significance for controlling water and soil pollution and improving the leaching rate of rare earths. In this paper, the column leaching test of ionic rare earth was carried out to study the evolution of the relationship between pore structure and permeability coefficient. In the process of MgSO4 solution and deionized water leaching, the T2 spectrum and inversion image at each time were obtained by nuclear magnetic resonance (NMR). Based on the fractal theory, the pore structure change of the inversion image was quantitatively analysed, and the permeability coefficient of samples at each time of different leaching agents was calculated by using supercritical Dubinin-Redushckevich (SDR) model to analyse the nuclear magnetic resonance T2 spectrum. The results show that in MgSO4 solution, the permeability coefficient of the sample changes significantly, and the growth rate of pore fractal dimension remains large. By discussing the evolution law of pore fractal dimension and seepage characteristics of ionic rare earth, the mathematical relationship between permeability coefficient and pore fractal dimension of mineral soil samples at different depths is fitted by polynomial function.